2015
DOI: 10.1007/s13280-015-0722-0
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable farming practices of the Chinese mitten crab (Eriocheir sinensis) around Hongze Lake, lower Yangtze River Basin, China

Abstract: Results of a survey of 156 Chinese mitten crab (Eriocheir sinensis) grow-out farms around Hongze Lake (118.48-118.72°E; 33.36-33.38°N) are reported. Area farmed has remained relatively unchanged but production (59 932 t in 2012) increased steadily over the last 7 years, indicative of the viability and sustainability of the farming system that has gradually replaced intensive Chinese major carp polyculture around Hongze Lake. Results showed that production range was 135-2400 kg ha -1 cycle -1 (mean 1144 ± 34). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 44 publications
3
38
0
Order By: Relevance
“…1). The relevant details of the mitten crab farming practices around Hongze Lake have been described previously (Wang et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). The relevant details of the mitten crab farming practices around Hongze Lake have been described previously (Wang et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Tables 1 and 2 show the amounts of TNL and TPL per hectare of mitten crab farming for each of the three feed types used and the total, respectively. In this computation the findings that 21% and 23% of farms surveyed used trash fish and pellet feed respectively, and 56% of farms surveyed used the combination of trash fish and pellet feed (Wang et al, 2016) were used. The analysis showed that there were no significant differences in TNL and TPL from mitten crab farms for different feed types (p N 0.05) (Tables 1 and 2).…”
Section: Evaluation Of the Changes In Total Nitrogen And Phosphorus Lmentioning
confidence: 97%
See 3 more Smart Citations